VD_FINDINFO HC / 2010 / 274 vom 23. März 2010 - VD Tribunal cantonal (2010)
MENACEDROIT PÉNAL, SURSIS À L'EXÉCUTION DE LA PEINE, PEINE PRIVATIVE DE LIBERTÉ, FIXATION DE LA PEINE | 180 CP, 41 al. 1 CP, 42 al. 1 CP, 47 CP